Anterior cruciate ligament repair with LARS (ligament advanced reinforcement system): a systematic review - Machotka Zuzana; Scarborough Ian; Duncan Will; Kumar Saravana; Perraton Luke (BMC, 2010)
Abstract Background Injury to the anterior cruciate ligament (ACL) of the knee is common. Following complete rupture of the ACL, insufficient re-vascularization of the ligament prevents it from healing completely, creating a need for reconstruction. A variety of grafts are available for use in ACL reconstruction surgery, including synthetic grafts. Over the last two decades new types of synthetic ligaments have been developed. One of these synthetic ligaments, the Ligament Advanced Reinforcement System (LARS), has recently gained popularity. The aim of this systematic review was to assess the current best available evidence for the effectiveness of the LARS as a surgical option for symptomatic, anterior cruciate ligament rupture in terms of graft stability, rehabilitation time and return to pre-injury function. Method This systematic review included studies using subjects with symptomatic, ACL ruptures undergoing LARS reconstruction. A range of electronic databases were searched in May 2010. The methodological quality of studies was appraised with a modified version of the Law critical appraisal tool. Data relating to study characteristics, surgical times, complication rates, outcomes related to knee stability, quality of life, function, and return to sport as well as details of rehabilitation programs and timeframes were collected. Results This review identified four studies of various designs, of a moderate methodological quality. Only one case of knee synovitis was reported. Patient satisfaction with LARS was high. Graft stability outcomes were found to be inconsistent both at post operative and at follow up periods. The time frames of rehabilitation periods were poorly reported and at times omitted. Return to pre-injury function and activity was often discussed but not reported in results. Conclusions There is an emerging body of evidence for LARS with comparable complication rates to traditional surgical techniques, and high patient satisfaction scores. However, this systematic review has highlighted several important gaps in the existing literature that require future prospective investigation. The findings of this review were equivocal with regards to other measures such as graft stability and long term functional outcomes. While the importance of rehabilitation following LARS is well recognised, there is limited evidence to guide rehabilitation protocols.